Administrative competencies and their relationship to time management for managers Middle schools from the point of view of teachers - Ahmed Naim Hassan, Lect.Dr; Waqar Youssef Abdul Khaleq, Lect.Dr (lark, 2023)
Generally speaking, administrative leadership greatly effects the future of the humanity civilization. Their decisions constitutes some differences between success and failure. This is an actual reality in our modern technical world. So the future of the world is controlled by the educated countries which have developed educated systems because they are considered the cornerstone and the beating heart for developing and promoting world. Any society, its importance lies in focusing on an important issue which effect the public institutions and achieve their aims, it represents:The level of the administrative competencies of the head masters of preparatory schools in Wassit from viewpoint of the members of faculty.The level of time administration for the head masters of preparatory schools in Wassit from viewpoint of the members of faculty.Introduce the relationship between the administrative competencies and time administration for the head masters of preparatory schools in Wassit from viewpoint of the members of faculty.The researcher adopts analytical descriptive method. The procedures include the research society which includes (1748), (988) male teachers and (760) female teachers. The sample involves (300) teachers (males and females), (170) male teachers and (130) female teachers.The date have been processed statistically by using statistical bag for science (Sbss). The results of the research displays: The level of the administrative competencies of the head masters of preparatory schools is medium and the level of time administration for the head masters of preparatory schools is good.  There is positive relationship between them
Keywords: the administrative competencies, time administration, and the head masters of preparatory schools.